Screening for spontaneous preterm birth by cervical length and shear-wave elastography in the first trimester of pregnancy - Feng Q. (2023)
Background: First-trimester cervical length for the prediction of spontaneous preterm delivery remains controversial. A better method for the measurement of the first-trimester cervical length and additional cervical ultrasound parameters for the identification of women at high risk for spontaneous preterm delivery are needed. Objective: This study aimed to compare the predictive value of cervical length measured by 2 different methods in the first trimester of pregnancy to predict spontaneous preterm delivery and to explore the potential value of first-trimester cervical shear-wave elastography for the prediction of spontaneous preterm delivery. Study Design: This was a prospective study in unselected singleton pregnancies at 11+0 to 13+6 weeks’ gestation. Cervical length was measured by the following 2 methods in the base-cohort population: (1) a linear distance between the 2 ends of the glandular area around the endocervical canal (single-line method: cervical length-s) and (2) a sum of the linear distance from the internal os to the greatest cervical curvature and the linear distance from this point to the external os (2-line method: cervical length-t). In a substudy, cervical shear-wave elastography scores for 9 regions of interest (inner, middle, and external parts of anterior lip, endocervical canal, and posterior lip) in midsagittal plane were also obtained by transvaginal ultrasonography. The screening performance of the first-trimester cervical length measured by the 2 different methods for the prediction of spontaneous preterm delivery was assessed by receiver operating characteristics curve analysis. The areas under the curves were compared using a DeLong test. The predictive performance of a soft cervix (mean elastography scores with multiple of median <5th, 10th, 15th, 20th, and 25th percentile) for spontaneous preterm delivery was also determined. Results: Among a total of 2316 included pregnancies, spontaneous delivery at <37 and <34 weeks’ gestation occurred in 111 cases (4.8%) and 20 cases (0.9%), respectively. In the total study population, when compared with the term delivery group, the median cervical length-t was shorter in women with spontaneous delivery at <34 weeks’ gestation (36.9 mm vs 35.1 mm; P=.015), but there was no clear correlation for cervical length-s. Receiver operating characteristics curves demonstrated that cervical length-t achieved better performance in predicting spontaneous delivery at <34 weeks’ gestation (area under the curve, 0.658 vs 0.573; P<.01) than cervical length-s. The best combined model to predict spontaneous delivery at <34 weeks’ gestation was provided by cervical length-t and history of preterm delivery (area under the curve, 0.692). In the substudy, a soft cervix with a mean elastography scores multiple of median <10th percentile had a relative risk of 7.8 (95% confidence interval, 2.1–28.6) for spontaneous delivery at <34 weeks’ gestation; the detection rate was 44.4% at a false-positive rate of 9.0%. Conclusion: The 2-line approach provides a better estimate of the actual first-trimester cervical length and achieves better performance as a screening tool for spontaneous preterm delivery at <34 weeks’ gestation than the conventional measurement. A soft cervix as determined by shear-wave elastograpthy in the first trimester is associated with an increased risk for subsequent spontaneous preterm delivery.